(untitled) (Medico Legal Update, 2020)
Objectives: Alternative plants Medicine has been considered one of the world’s most important solutions to female reproductive diseases. The goal of the current study however, was to evaluate the mains histological changes that follow the use of seeds of (Trigonellatibetana) on ovary folliculogenisis. Method: Twelve’s female healthy rabbits, in animal house all experimental animals have been adapted. For this study, animals were taken distributed into two groups, control administrated by distal water (5 ml/ kg b.w) and treatment group was administered by Trigonellatibetana extract at a dose of 2g/kgb.w/orally administration during 2 week for 3 time daily. Results: The present study finding the numerouschanges happened in the ovary, the mains variance has been noticed increase the numbers of primordial and atretic follicles in treatment group and increase in size of follicles. Moreover, the theca interna was thickness and has a thicker layers of collagen than control group. Conclusions: Such results indicate that (Trigonellatibetana) was considered to be suitable for early fertility period arrival.